The problem of gastroptosis as a manifestation of undifferentiated connective tissue dysplasia in the clinical practice of pediatric gastroenterologist - O.M. Shulhai; A.B. Kabakova; L.A. Klym; A.-M.A. Shulhai; K.T. Glushko (Zaslavsky O.Yu., 2018)
In the article, the authors describe a clinical case of undifferentiated connective tissue dysplasia in 10- and 15-year-old girls. This pathology is common because it has a lot of clinical, morphological and visceral manifestations, but it is hard to diagnose. Many chronic diseases have been formed based on this pathology. Clinical cases in this article describe confirmed gastroptosis (greater curvature of the stomach is displaced downwards, below the level of the iliac crests in standing position) as one of the visceral manifestations of undifferentiated connective tissue dysplasia, laboratory and instrumental findings that help to diagnose this syndrome. Gastroptosis occurs in children with asthenic type of constitution (elongated limbs, thin body, small chest, narrow shoulders, hypermobility of the joints). It comes from weak development of muscle and connective tissues so they can not endure overload, resulting is many problems, including the gastroptosis, visceroptosis etc. There are many causes of gastroptosis: congenital anomalies of the ligamentous apparatus structure, maternal disease during pregnancy, surgical intervention, sharp decrease in body weight, vitamin and proteins deficiency, irrational nutrition, lengthening the mesentery of an organ such as large intestine. If we know clinical manifestations and features of undifferentiated connective tissue dysplasia, it will allow diagnosing this pathology in a timely manner and will help more fully provide medical care to such patients, carry out their rehabilitation, psychological adaptation, and prevent early development of disability.